UPAYA PEMBERDAYAAN MASYARAKAT MELALUI HOME INDUSTRY PEMBUATAN TAHU DI MUARA CIUJUNG KECAMATAN RANGKASBITUNG - Piniah Piniah; Syadeli Hanafi; Mochamad Naim (Politeknik Negeri Sriwijaya, 2023)
Empowerment is an effort to build community capacity, by encouraging, motivating, awakening, awareness of the potential they have and trying to increase and develop this potential so that it becomes real. This research is an empowerment effort carried out to overcome the problems that occur in the Ciujung Muara village, starting from the low level of community skills and the large number of unemployed people in the Ciujung Muara village. To examine the process of implementing this research examines the problem Through Tofu Making Home Industry, (3) Empowerment Indicators. The method used by the author in this study uses a descriptive method with a qualitative approach, where data is obtained from observations, interviews and documentation. The data source for this research consisted of 1 tutor and home industry owner, 4 home industry owners, and 5 home industry employees. The results of this study indicate (1) Community Empowerment Efforts Through Tofu Making Home Industry have been going well. (2) the results of Community Empowerment Efforts Through Tofu Making Home Industry make people empowered and independent so that they are able to establish their own home industry. (3) people have freedom of mobility, as well participating in the empowerment process, as well as limited capital to open their own home industry. Keywords: Community, Empowerment, Home Industry, freedom of mobility, method